EFEKTIVITAS PENYULUHAN DALAM JARINGAN TERHADAP PENGETAHUAN PEMELIHARAAN KEBERSIHAN GIGI DAN MULUT SERTA KETERAMPILAN MENYIKAT GIGI SISWA SMK PARIWISATA KERTAYASA SINGAKERTA UBUD - Regina Tedjasulaksana; I Nyoman Wirata (Jurnal Kesehatan Gigi (Dental Health Journal), 2022)
Dental and oral hygiene is one of the elements in personal hygiene which is very important during the Covid 19 pandemic in order to avoid dental and oral diseases and reduce the risk of spreading covid 19. One of the efforts to increase knowledge and skills in brushing teeth is through online counseling (online). The purpose of this study was to determine the effectiveness of online dental and oral hygiene counseling on the knowledge and skills of brushing teeth for students of SMK Wisata Kertayasa Singakerta Ubud. This type of research is a pre-experimental one group pretest and posttest design. The sampling technique was purposive sampling, as many as 96 respondents. Data were analyzed by Wilcoxon test. The results showed that the average value of knowledge about dental and oral hygiene before being given online counseling was 68.07±13.21 with sufficient category and after counseling it was 76.34±12.15 with good category. The average value of brushing skills before being given counseling and demonstration of brushing teeth was 53.60±20.74 in the category of needing guidance and after counseling was 90.54±13.28 in the very good category. The results of the different test with the Wilcoxon testobtained p value = 0.000 (0.05). So there is a significant difference in the value of knowledge and skills of brushing teeth before and after online counseling.